Seasonal reversal in phytoplankton assembly mechanisms: stochastic dominance in autumn vs. deterministic control in spring within the middle and lower reaches of the Yellow River - Zeng, Dahai; Ding, Houkuan; Tang, Yuanyuan; Gao, Yunni; Jin, Jialin; Gao, Xiaofei; Zhang, Jingxiao; Yuan, Huatao; Dong, Jing; Li, Xuejun (Frontiers in Microbiology, 2025)
Phytoplankton communities play a crucial role in riverine ecosystems, yet their assembly mechanisms in high-silt environments remain poorly understood. This study investigated seasonal variations in phytoplankton community structure and assembly mechanisms in a riverine environment with high silt loads. Phytoplankton and physicochemical water quality factors were analyzed in the middle and lower reaches of the Yellow River during two seasons: November 2023 (autumn) and April 2024 (spring). A total of 110 algal species from seven phyla were identified, with Chlorophyta being predominant in species richness and Cyanophyta in cell density. Both species richness and abundance were lower in autumn than in spring. The α-diversity analysis revealed that the Pielou’s eveness index was significantly higher in spring compared to autumn. Non-metric multidimensional scaling (NMDS) based on Bray–Curtis distances showed significant seasonal differences in phytoplankton community composition. Furthermore, β-diversity decomposition analysis revealed that turnover was the dominant component in both seasons, but the proportion of nestedness was significantly higher in spring compared to autumn (p < 0.05). Based on the analyses of the dispersal–niche continuum index (DNCI) and the modified stochasticity ratio (MST), this study demonstrates pronounced seasonal variations in the assembly mechanisms governing phytoplankton communities in the middle and lower reaches of the Yellow River. In autumn, stochastic processes, primarily driven by dispersal, accounting for 58.85% of the community assembly. In contrast, deterministic processes, largely shaped by niche selection, contributing 65.05% to the community assembly in spring. The community structure of phytoplankton in this region is shaped by the combined effects of geographical factors, elevation, and environmental variables, with particularly pronounced seasonal variations in environmental drivers—total nitrogen (TN) emerges as the primary factor influencing autumn community assembly, while spring community structure is mainly regulated by silica (SiO₂) and pH. This study deepens the understanding of phytoplankton assembly mechanisms in sediment-rich rivers and provides fundamental data for phytoplankton construction mechanisms and aquatic biodiversity conservation in the middle and lower reaches of the Yellow River.